Roads diverged in a wood: Proteins and RNAs encoded by cytochrome b (CYTB) gene in health and disease - Cijie Du; Baodan Chen; Yile Huang; Wenxi Liang; Ying Hua Su; Xingguo Liu (Clinical and Translational Discovery, 2025)
Abstract Background The cytochrome b (CYTB) gene, a crucial component of the mitochondrial genome, plays a multifaceted role in cellular metabolism, energy production and various biological processes. Main body It is well known that the CYTB gene encodes a subunit of complex III in the electron transport chain, which is vital for the oxidative phosphorylation process and ATP generation. Various studies report that the CYTB gene not only encodes a core protein in the mitochondrial respiratory chain but also produces a long non‐coding RNA called lncCYTB, which participates in a variety of physiological and pathological processes. Inspiringly, a study has recently revealed that the CYTB gene also encodes a novel 187 amino acid long polypeptide, CYTB‐187AA, a mitochondrial DNA‐encoded protein produced by cytosolic translation and important for early mammalian development. Conclusion This review will provide insight into the functional and expression properties of the CYTB gene, as well as its unique non‐coding RNA signature, and describe the diseases associated with the CYTB gene, ranging from mitochondrial dysfunction to more complex genetic disorders.